Engineering hydrology of Kodku Khola Basin, Lalitpur, Nepal - Maharjan, Laxmi Devi; Dangol, Vishnu (Bulletin of the Department of Geology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Not only in rural areas but also in urban areas, vast number of people lack access to safe drinking water. The city of Lalitpur is in severe deficit of drinking water for its population. Hydrological study of the Kodkhu Khola Basin near the Lalitpur City was carried out in pre-feasibility level. Rainfall data were analysed to estimate future rainfall trend that would determine the rainfall intensity, frequency, maximum and minimum rainfalls. The discharge of the river was estimated by float method. About 70% of flow in the river occurred in monsoon from June to September. The mean yearly rainfall of ten years of record was 1238 mm in the Khumaltar Station and 1494 mm in the Godawari Station. The intensity of the maximum rainfall in a day of each of ten years fell in the heavy category and most of the years fell in the normal year category. Maximum rainfall of 100 year's recurrence interval will have magnitude of 1595 mm. The discharge ranged from 17.35 m3/s to 56.94 m3/s in the upstream reaches. The amount of rainfall and discharge is thought to be sufficient for maintaining the reservoir for drinking water supply in Lalitpur city and the Kodku Khola is appreciable for the drinking water source. doi: 10.3126/bdg.v10i0.1426 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 107-116